Quando incluir é excluir: um estudo discursivo do surdo na escola - Gondim, Onilda Aparecida (2011)
This dissertation discussed the process of inclusion of deaf students of a regular school by analyzing its possible effects for the teacher, the students and the interpreters. The research aimed at answering how a deaf student constitutes himself and is constituted in the Portuguese classroom. It was dealt with a hypothesis under which deaf students seemed to suffer from the discursive effects of subjective rarefaction, what did not allow them to have a relationship with knowledge and its production that could be considered appropriate. One of the consequences of such a relationship was that it was not possible to consider the deaf students included in the learning process. Theoretically, the research was founded in the concepts of the French Discourse Analysis as conceived by Michel Pêcheux, especially those ones related to the so called third stage of his work. Studies undertaken by Authier Revuz on enunciation and specialized readings on deafness were also taken into account. Methodologically, classes were recorded and transcribed during a period of approximately four months. In addition, interviews and field notes were also used as tools to collect data. The analysis was divided into two different moments. In the first one, utterances were analyzed in order to discuss the way the projection of images, which constitutes the functioning of classroom discourse, influenced the relationship among the teacher, the deaf and the interpreters. By doing so, it was possible to realize the images each participant has from each other. In the second one, the way each participant addresses himself towards each other was emphasized. Such an analysis helped the researcher understand how the deaf constituted and were constituted as students in the classroom. Results have shown that the way participants address themselves in the classroom is not enough to make the deaf assume a discursive position as a student who could produce some kind of knowledge in the Portuguese Language classroom.